Pengaruh Corporate Governance dan Financial Performance Terhadap Cost of Equity dengan Earnings Quality Sebagai Variabel Intervening Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2023 - Chandra Situmeang; Andico Sihombing (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The aims of this study to identify, examine and explain the influence of corporate governance and financial performance on cost of equity with earnings quality as an intervening variable. Population of this study is manufacturing companies on the Indonesia Stock Exchange in 2023. The purposive sampling technique was used in selecting the sample so that a research sample of 187 companies was obtained. The data analysis technique in this study was path analysis with the SEM PLS approach and using Smart PLS 4.0 software. Results of this study concludes that corporate governance has an effect on earnings quality, financial performance has no effect on earnings quality, corporate governance has an effect on cost of equity, financial performance has an effect on cost of equity, earnings quality has no effect on cost of equity, corporate governance has no effect on cost of equity through earnings quality and financial performance has no effect on cost of equity through earnings quality. The conclusion of this study is that corporate governance has an effect on earnings quality, financial performance has no effect on earnings quality, corporate governance has an effect on cost of equity, financial performance has an effect on cost of equity, earnings quality has no effect on cost of equity. Earnings quality cannot mediate the influence of corporate governance or financial performance on cost of equity.